Detection of Postcoronary Stent Complication: Utility of 64-Slice Multidetector CT. (1st July 2012) - Bharati, Alpa; Merchant, Suleman; Suvarna, Tilak; Parashar, Neha
Abstract : Coronary stent fracture is a known complication of coronary arterial stent placements. Multiple long-term risks are also associated with drug eluting stents. 64-slice multidetector CT (MDCT) coronary angiography has been shown to detect poststent complications such as instent stenosis, thrombosis, stent migration and stent fractures. We report a case of stent fracture in a patient who underwent RCA stenting with associated RCA perforation and almost complete thrombosis of the RCA and peristent fibrinoid collection. This is a rare case of stent fracture with perforation of the RCA. The paper highlights the role of 64-row multidetector computed tomography (MDCT) in evaluation of such poststent placement complications.